A Project-Based Learning Approach to Supply Chain Mapping Education - Ashraf, Muhammad Hasan; Özpolat, Koray; Yalçın, Mehmet G.; Shah, Piyush (Elsevier, 2025)
Although recent disruptions have revealed the importance of supply chain mapping, there is a lack of academic content in this domain. This is evident because supply chain management textbooks and pedagogical articles offer limited practical guidance on developing supply chain maps. Neither do Harvard Business Publishing and the Case Center cases. The main reason for this scarcity is the challenge of integrating supply chain mapping into the course curriculum. To address this and enrich academic content, we introduce a Supply Chain Mapping Project based on a Project-Based Learning approach to instruct undergraduate business students in fundamental mapping skills and raise awareness of the complexities involved in producing high-quality maps. The project is implemented in two upper-level undergraduate courses. The project’s effectiveness is assessed through the post-project survey responses. Results indicate that students were actively engaged throughout the project. Similarly, survey results from one of the similar courses offered in the subsequent semester validate the effectiveness of the project. Given the rising demand for supply chain talent within the management domain, this project will enhance the management/ supply chain management curricula at business schools. The benefits and challenges of the proposed approach are discussed in the paper.
Keywords: Supply chain mapping; Management; Project-based learning; Commercial software